Language and mathematics: dialogue on a recent book. Speaking of Pier Luigi Ferrari’s Educazione matematica, lingua, linguaggi. Costruire, condividere e comunicare matematica in classe (Torino, UTET, 2021) - Pietro Di Martino; Francesca Gallina (Italiano a scuola, 2021)
This paper represents a two-part dialogue between an expert on the didactics of mathematics and an expert on language teaching about the relationship between language and mathematics at school, in the light of the stimuli offered by the recent book of the mathematician Pier Luigi Ferrari, Educazione matematica, lingua, linguaggi. Costruire, condividere e comunicare matematica in classe.